Determination of Monensin in Bovine Tissues: A Bridging Study Comparing the Bioautographic Method (FSIS CLG-MON) with a Liquid Chromatography-Tandem Mass Spectrometry Method (OMA 2011.24). (23rd November 2019) - Mizinga, Kemmy M; Burnett, Thomas J; Brunelle, Sharon L; Wallace, Michael A; Coleman, Mark R
Abstract: The U.S. Department of Agriculture, Food Safety Inspection Service regulatory method for monensin, Chemistry Laboratory Guidebook CLG-MON, is a semiquantitative bioautographic method adopted in 1991. Official Method of Analysis SM (OMA) 2011.24, a modern quantitative and confirmatory LC-tandem MS method, uses no chlorinated solvents and has several advantages, including ease of use, ready availability of reagents and materials, shorter run-time, and higher throughput than CLG-MON. Therefore, a bridging study was conducted to support the replacement of method CLG-MON with OMA 2011.24 for regulatory use. Using fortified bovine tissue samples, CLG-MON yielded accuracies of 80–120% in 44 of the 56 samples tested (one sample had no result, six samples had accuracies of >120%, and five samples had accuracies of 40–160%), but the semiquantitative nature of CLG-MON prevented assessment of precision, whereas OMA 2011.24 had accuracies of 88–110% and RSDr of 0.00–15.6%. Incurred residue results corroborated these results, demonstrating improved accuracy (83.3–114%) and good precision (RSDr of 2.6–20.5%) for OMA 2011.24 compared with CLG-MON (accuracy generally within 80–150%, with exceptions). Furthermore, χ 2 analysis revealed no statistically significant difference between the two methods. Thus, the microbiological activity of monensin correlated with the determination of monensin A in bovine tissues, and OMA 2011.24 provided improved accuracy and precision over CLG-MON.